Des gens « ordinaires » et des révélateurs de conspiration . . . Commentaire anthropologique sur la posture des intervenants lors d’une commission parlementaire - Cook, Mathieu (Anthropologica, 2019)
This article presents some of the results of an analysis of the briefs submitted to the parliamentary committee concerning the Agreement-in-Principle of General Nature between the First Nations of Mamuitun and Nutashkuan and the Government of Quebec and the Government of Canada. We focus on the postures that the social actors displayed in their briefs. We begin with a reflection regarding the concept of posture, as well as details about the methodological orientation of this research. Seven types of postures are examined, including that of paranoid spokesman (Hofstadter 1996), which we discuss more in depth.